COOPERATIVE MEMBER SAVINGS GUARANTEE AS A FORM OF LEGAL PROTECTION IN THE MAá¹¢LAá¸¤AH PERSPECTIVE - Fadillah Mursid; Mohamad Anton Atoillah; Luqman Nurhisam (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis research discusses the guarantee of cooperative member deposits. This research has a background that in recent times, there have been many cases of problematic cooperatives in Indonesia, with material losses of members reaching trillions. This research study examines how the guarantee of cooperative members' deposits is a form of legal protection from Maá¹£laá¸¥ah 's perspective. The research method used is qualitative, normative research with analytical descriptive specifications; the legal materials used are primary legal materials (related legal rules) and secondary (various literature and research results. The results of this study indicate that currently, in Indonesia, no regulation provides explicitly a legal basis for the certainty of guaranteeing deposits of cooperative members. So, for the benefit of the government, laws related to deposit guarantees for cooperatives must be issued as a form of legal protection through the fulfilment of citizens' rights. One of the guarantee models that can be used is an explicit guarantee model with restrictions on the guarantee amount.Â Keywords: Savings Guarantee; Cooperative; Maá¹£laá¸¥ah.